Study on Properties of Environment-friendly Concrete Containing Large Amount of Industrial by-products. Issue 1 (October 2015) - Fujiwara, H; Maruoka, M; Sadayama, C; Nemoto, M; Yoshikawa, K; Yamaji, M
Abstract: This study aims to reduce CO2 discharged from the cement and concrete industries by effective use of industrial by-products, such as fly ash, blast furnace slag, and so on. In this paper, the properties of concrete containing large amount of industrial by-products and very small amount of alkaline activator including cement or sludge from ready mixed concrete plant are analyzed. As the result, it was confirmed that concretes containing large amount of industrial by-products can achieve sufficient compressive strength. However, these concretes showed poor frost resistance. It was thought that the reason was coarsening of air void system and this caused their poor frost resistance. Therefore, in order to micronize the air void system and improve frost resistance, the combination of air entraining agent and antifoaming agent was applied. By this method, it was confirmed that the frost resistance of some these concrete improved. In this study, other properties of these concretes, such as fresh properties and other durability were evaluated and it was confirmed that these concretes show sufficient properties.